Utility of the cold pressor test to predict future cardiovascular events. (3rd April 2019) - Pouwels, Sjaak; Van Genderen, Michel E.; Kreeftenberg, Herman G.; Ribeiro, Rui; Parmar, Chetan; Topal, Besir; Celik, Alper; Ugale, Surendra
ABSTRACT: Introduction : The cold pressor test (CPT) is a common and extensively validated test, which induces systemic stress involving immersion of an individual's hand in ice water (normally temperature between 0 and 5 degrees Celsius) for a period of time. CPT has been used in various fields, like examining effects of stress on memory, decision-making, pain and cardiovascular health. Areas covered : In terms of cardiovascular health, current research is mainly interested in predicting the occurrence of cardiovascular (CV) events. The objective of this review is to give an overview of the history and methodology of the CPT, and clinical utility in possibly predicting CV events in CAD and other atherosclerotic diseases. Secondly, we will discuss possible future applications of the CPT in clinical care. Expert opinion : An important issue to address is the fact that the physiology of the CPT is not fully understood at this moment. As pointed out multiple mechanisms might be responsible for contributing to either coronary vasodilatation or coronary vasoconstriction. Regarding the physiological mechanism of the CPT and its effect on the measurements of the carotid artery reactivity even less is known.